Hybrid work, flexible working hours and career progression: The perspective of women employees during the COVID-19 pandemic - Rebelo, G.; Almeida, A. R.; Pedra, J. P. (Employee Relations, 2026)
Purpose The impact of technological change on work must be related to the objective of guaranteeing equal opportunities at work. Teleworking and hybrid work seem to offer workers unprecedented flexibility. The COVID-19 pandemic offered the opportunity to investigate this phenomenon. In post-pandemic period, with the massive emergence of hybrid work, it is therefore necessary to understand whether it can be valued as an instrument for strengthening equality at work between women and men, allowing women to guarantee equal career progression. Design/methodology/approach The aim of this article is to identify, from the perspective of working women, which management measures are most important to ensure greater gender equality in career progression. In addition to a documentary analysis, this article presents an analysis of some of the results of an online survey carried out during the COVID-19 pandemic, between 15 November and 16 December 2021, answered by women with an employment contract. Findings The study reveals that the women surveyed consider flexible working hours and the implementation of a hybrid working model (mixed face-to-face/remote) to be priority measures to ensure equality between men and women in career progression. Furthermore, this study reveals that it is mainly women who are married or in a consensual union who consider these measures to be priorities. Originality/value The findings provide a new perspective on the potential of the hybrid work model and flexible working hours, helping to strengthen gender equality in career progression.